Facile Green, Room-Temperature Synthesis of Gold Nanoparticles Using Combretum erythrophyllum Leaf Extract: Antibacterial and Cell Viability Studies against Normal and Cancerous Cells - Olufunto T. Fanoro; Sundararajan Parani; Rodney Maluleke; Thabang C. Lebepe; Jose R. Varghese; Vuyo Mavumengwana; Oluwatobi S. Oluwafemi (MDPI AG, 2021)
We herein report a facile, green, cost-effective, plant-mediated synthesis of gold nanoparticles (AuNPs) for the first time using Combretum erythrophyllum (CE) plant leaves. The synthesis was conducted at room temperature using CE leaf extract serving as a reducing and capping agent. The as-synthesized AuNPs were found to be crystalline, well dispersed, and spherical in shape with an average diameter of 13.20 nm and an excellent stability of over 60 days. The AuNPs showed broad-spectrum antibacterial activities against both pathogenic Gram-positive (Staphylococcus epidermidis (ATCC14990), Staphylococcus aureus (ATCC 25923), Mycobacterium smegmatis (MC 215)) and Gram-negative bacteria (Proteus mirabilis (ATCC 7002), Escherichia coli (ATCC 25922), Klebsiella pneumoniae (ATCC 13822), Klebsiella oxytoca (ATCC 8724)), with a minimum inhibition concentration of 62.5 µg/mL. In addition, the as-synthesized AuNPs were highly stable with exceptional cell viability towards normal cells (BHK- 21) and cancerous cancer cell lines (cervical and lung cancer).